PENDIDIKAN ISLAM DAN PERUBAHAN SOSIAL - Nasrullah, Amin (AZKIYA, 2019)
Education and society have a reciprocal, mutual influence (reciprocal) relationship. This article discusses the relationship between Islamic education and social change in two directions at once, namely what and how the role of Islamic education in driving social transformation (reconstruction) and conversely, what role should be carried out by the Islamic education in the midst of changing social life. The analysis in this article was developed using the assumptions of the categorization of education ideology as used by Henry Giroux and Aronowitz, that divided educational ideology into three major streams, namely conservative, liberal, and critical. The mapping of the ideological and educational paradigms is carried out to review the position of Islamic education in the great currents of educational ideology, and the possible choices that can be taken so that Islamic education is able to play its function, namely the function of equality and social egalitarianism. Likewise the function and role of Islamic education in social transformation, to rebuild (reconstruction) systems and social order that are balanced, democratic, and just